Temporal Dynamics of Internal Financing on Financial Performance Within a Corporate Governance Sustainability Framework: Evidence from Listed Real Sector Non-Financial Firms at the Nairobi Securities Exchange (NSE) (Global Journal of Management and Business Research, 2025)
There is growing recognition of the central role corporate governance plays in providing specialized services that align firms towards accountable and transparent financial practices. What is not clear, however, is the conditional effect of corporate governance on the causal link involving internal financing and financial performance. Therefore, this study exploits the principles underlying the Agency and Pecking Order Theories to probe how corporate governance conditions the effect of retained earnings, a popular internal financing source, on the financial performance of real-sector non-financial firms listed at the Nairobi Securities Exchange (NSE). The study employs a causal-explanatory design that targets 51 real-sector non-financial firms listed at the NSE. A sampling frame defined for the period 2016 to 2022 inclusive is used to identify 42 firms with complete and suitable financial records that constituted the secondary data.
Keywords: internal financing; corporate governance; financial performance; retained earnings; sustainability framework